One new genus and three new species of subfamily Mictinae (Coreidae - Heteroptera) for Vietnam - Khuong, Dang Duc (Academia Journal of Biology, 2015)
One new genus and three new species of subfamily Mictinae (Coreidae - Heteroptera) for Vietnam